2011
DOI: 10.4103/0973-7847.79100
|View full text |Cite
|
Sign up to set email alerts
|

A review on Balanites aegyptiaca Del (desert date): phytochemical constituents, traditional uses, and pharmacological activity

Abstract: Balanites aegyptiaca Del. (Zygophyllaceae), known as ‘desert date,’ is spiny shrub or tree up to l0 m tall, widely distributed in dry land areas of Africa and South Asia. It is traditionally used in treatment of various ailments i.e. jaundice, intestinal worm infection, wounds, malaria, syphilis, epilepsy, dysentery, constipation, diarrhea, hemorrhoid, stomach aches, asthma, and fever. It contains protein, lipid, carbohydrate, alkaloid, saponin, flavonoid, and organic acid. Present review summarizes the tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
113
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(143 citation statements)
references
References 43 publications
14
113
1
1
Order By: Relevance
“…Saponins components of the methanol extract may be responsible for the elucidated cytotoxic effectiveness. The present data are in close agreement with reported findings which showed that B. aegyptiaca saponin mixture demonstrated cognizable anticancer effects in human A549 nonsmall-cell lung cancer (IC 50 0.09 µg/mL) and U373 glioblastoma (IC 50 0.15 µg/mL) human carcinoma cell lines [3] comparing with IC 50 0.6 and 2.04 µg/mL against H460 lung cell line of both chloroform and methanol extracts, respectively in the present results. In vivo saponin prolonged the survival time of mice bearing murine L1210 leukemia grafts exactly as vincristine [3], which is in good agreements with present finding where methanol fraction displayed remarkable in vitro cytotoxic effect against lymphoblastic leukemia (1301) cell line.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Saponins components of the methanol extract may be responsible for the elucidated cytotoxic effectiveness. The present data are in close agreement with reported findings which showed that B. aegyptiaca saponin mixture demonstrated cognizable anticancer effects in human A549 nonsmall-cell lung cancer (IC 50 0.09 µg/mL) and U373 glioblastoma (IC 50 0.15 µg/mL) human carcinoma cell lines [3] comparing with IC 50 0.6 and 2.04 µg/mL against H460 lung cell line of both chloroform and methanol extracts, respectively in the present results. In vivo saponin prolonged the survival time of mice bearing murine L1210 leukemia grafts exactly as vincristine [3], which is in good agreements with present finding where methanol fraction displayed remarkable in vitro cytotoxic effect against lymphoblastic leukemia (1301) cell line.…”
Section: Discussionsupporting
confidence: 82%
“…The present results pointed out that antioxidants might oppose reactive free radicals species, which ultimately stimulates stress-induced pathways and hence hinders the pathogenic effect of glucose. In spite that chloroform extract exhibited the highest scavenging activity due to its phenolics content, which is compatible with previous reports [3], the methanolic extract, which is moderately active as antioxidant exhibited the highest antidiabetic activity (Figure 6). The results indicated that the antidiabetic activity is not directly proportion to the free radical scavenging activity.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Its fruit, bark and other parts have lethal properties to snail intermediate hosts, schistosome miracidia and cercariae, and the cercariae of other trematodes [17] . Nevertheless, the molluscicidal and cercariacidal properties of the plant have not been studied in Ethiopia.…”
Section: Schistosoma Mansonimentioning
confidence: 99%
“…It is known as ' Aduwa' in Hausa, 'Utazi' in Igbo, and 'Teji' in Yoruba. Balanites aegyptiaca (L) Del has a long history of traditional uses for wide ranges of disease [3]. Anti-diabetic activity of Balanites aegyptiaca (L) Del extracts have been reported in both diabetic mice and rats [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%